Thyroid eye disease presenting with superior rectus/levator complex enlargement. (2nd January 2020) - Wang, Yao; Mettu, Pradeep; Broadbent, Talmage; Radke, Phillip; Firl, Kevin; Shepherd, J. Banks; Couch, Steven M.; Nguyen, Angeline; Henderson, Amanda D.; McCulley, Timothy; McClelland, Collin M.; Mokhtarzadeh, Ali; et al.
ABSTRACT: Purpose : To describe the demographic and clinical characteristics of patients with thyroid eye disease (TED) who present with predominate superior rectus/levator complex involvement. Methods : A multi-institutional retrospective review was performed to identify patients with TED who presented with superior isolated or predominate rectus/levator involvement. Baseline and subsequent visits were reviewed to characterize the clinical course. Results : Nineteen patients were identified. All patients had imaging demonstrating an enlarged levator/superior rectus complex. At presentation, the mean clinical activity score (CAS) was 2.1 (range: 0–5). Nineteen (100%) patients had proptosis on the affected side. Lid abnormalities, including upper/lower eyelid retraction and ptosis were higher on affected side compared to the unaffected side. Eleven (58%) patients had vertical misalignment. Mean thyroid stimulating immunoglobulin (TSI) was 3.7 (range: 1–7.1). Mean follow-up time was 18 months (range: 0–60 months). At last follow-up, the mean CAS was 1.3 (range 0–5). Ten (53%) patients had proptosis. Eleven (58%) patients had vertical misalignment. Repeat imaging in eight patients showed interval enlargement of other extraocular muscles. Conclusions : The presentation of TED with superior rectus/levator complex enlargement may be under-appreciated. Orbital imaging, as well as laboratory evaluation, may help support a diagnosis of TED. In the setting of abnormal TSI and/or thyrotropin receptor antibody, presence of upper eyelid retraction, and an otherwise unremarkable laboratory and systemic evaluation, a presumptive diagnosis of TED may be made, and the patient can be followed closely, as he/she is likely to develop involvement of other extraocular muscles, consistent with a more typical presentation of TED.